Kontribusi Muhasabah dalam Mengembangkan Resiliensi Pada Orang Tua Anak Berkebutuhan Khusus - Fatma Laili Khoirun Nida (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2021)
The phenomenon of the poor quality of parental care for children with disabilities makes resilience one of the psychological capital that contributes to improving the quality of care. This study describes how through a muhasabah intervention in Blimbingrejo Village, Nalumsari District, Jepara Regency. The purpose of this study was to provide information for parents of children with special needs about muhasabah interventions in developing the resilience abilities of parents when carrying out their care. The urgency of this research is to reduce parenting stress experienced by parents because of the developmental barriers of their children. This research is qualitative with a case study approach through in-depth interviews and observation techniques. The study results explain that the condition of children with special needs is often a stressor for their parents. However, parents can live with complete steadfastness as a form of their resilience. The pattern of resilience formed is supported mainly by thinking about what they are trying to do. There are indications of the meaning of resilience factors in the practice of muhasabah in the form of the ability to regulate emotions, develop optimism and empathy, control impulses and causal analysis, good self-efficacy and take wisdom as an indication of aspects of the reaching out process. The results of this study are helpful information in developing the concept and practice of caring for children with special needs.